The Influence Of Brand Ambassadors On Purchase Decisions With Price Mediation Moderated By The Quality Of Kahf Face Wash Soap Products - Muslihat, Rivaldi; Permana, Muhamad Rizki; Irsyad, Saktian (Lentera Ilmu Nusantara, 2024)
The purpose of this study is to determine the influence of brand ambassadors on purchase decisions with price mediation moderated by the quality of face wash soap. The research design used in this study is quantitative. The subject of the study is consumers who use Kahf face soap products and the objects in this study are. Brand Ambassador, to purchase decisions with price mediation that moderates product quality. The sample in this study amounted to 102 respondents. Data were collected using questionnaires and expressed on the Likert scale. The results of the study showed that: that brand ambassador (X) had a negative and insignificant effect on the purchase decision (Y), price (Z) had a positive and significant effect on the purchase decision (Y), product quality (M) had a positive effect on the purchase decision (Y).